Susceptibilidade microbiana in vitro ao extrato acético de aipo em pó e o impacto sensorial quando aplicado em linguiça frescal de frango - Mattos, Gisely de (2022)
Eating habits have changed over the decades in pursuit of a healthier diet. Based on the consumer’s appraisal, food operators have move efforts to replace total or partially chemically synthesized preservatives with natural technology alternatives. Under this scope, this work aimed to evaluate i) in vitro microbial susceptibility to powder celery acetic extract (PCAE) on foodborne chicken’s related microorganisms: Salmonella Typhimurium (ATCC 14028), Escherichia coli (ATCC 25922), Listeria innocua (ATCC 33090), Pseudomonas aeruginosa (ATCC 27853), Staphylococcus aureus (ATCC 25923) and Clostridium perfringens (ATCC 13124); ii) produce fresh chicken sausage with PCAE and evaluate the effect on its sensorial attributes; iii) evaluate the physicalchemical and microbiological parameters of sausages. The turbidity method was used to evaluate the microbial susceptibility to PCAE. For that, PCAE was outlined ranging concentrations from 0.5 to 3.5% in brain-heart-infusion-broth (BHI), raising up 0.5% from tube to tube. Tubes absent of PCAE and absent of inoculum were included as control and blank, respectively. Potentially dosage to achieve microbial control was expressed considering three categories: i) susceptible; ii) partially susceptible; iii) resistant. In an in-situ trial, five formulations of fresh chicken sausage were developed: blank (B): absent of curing salt, sodium lactate and PCAE; Control (C): with 0.15 % of curing salt and 2.0 % of sodium lactate; Treatment 1 (T1): with 0.15 % of curing salt and 2.5 % of PCAE; Treatment 2 (T2): with 0.15% curing salt and 3.5 % of PCAE; Treatment 3 (T3): with 4.5 % of PCAE. The in vitro trial revealed that S. aureus and C. perfringens showed resistance up to 5.0 % of PCAE. P. aeruginosa, S. Typhimurium, L. innocua and E. coli showed partial susceptibility at 2.5to 5.0 % of PCAE. None of the microorganisms tested were susceptible to PCAE. All produced sausages complied to the microbiological and physical-chemical standards, prescribed by Brazilian legislation; however, the nitrite concentration in T1, T2 and T3, overtook the prescribed upper limit. The addition of 2.5% and 3.5% of PCAE did not negatively influence the sensory attributes of the sausage and reduced its weight loss during cooking. Thus, PCAE can partially control the growth of foodborne chicken’s related microorganisms without interfering on its sensory attributes, contributing to the microbiological safety.